Miskonsepsi Pemahaman Materi Bangun Datar Dengan Penerapan Teori Polya di PGMI 3 UINSU - Nurhafizah Nurhafizah; Rora Rizki Wandini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Students' lack of understanding of a concept is usually called a misconception. This research aims to determine misconceptions about understanding plane material by applying polya theory at PGMI 3 State Islamic University of North Sumatra. The subjects in this research were 4 PGMI 3 UINSU students. The type of research used is qualitative descriptive research. Data collection in this research was carried out using observation and test methods. The results of the research showed that there were student misconceptions in working on plane material problems with the application of polya theory, including: misconceptions about signs and misconceptions about work procedures. This misconception occurs because students are not careful and do not understand the concepts in working on flat shapes using polya theory.